INTERIORITY OF PUBLIC SPACE IN THE DEAF EXHIBITION CENTER IN BEKASI - Rachmita Maun Harahap; Imam Santosa; Deddy Wahjudi; Widjaja Martokusumo (SINERGI, 2019)
The study aims to show the implementation of Deaf Space design guidelines application in the Deaf Exhibition Center building. Even to increase society's understanding of the need for public space access facilities for hearing disabilities. The relation between persons with hearing disabilities and space is the most fundamental thing in creating a space experience (interiority). Interiority is processed prioritizing high visual orientation, and encourages the totality of other sensory experiences based on the philosophy of Deaf Space. In terms of interior design, persons with hearing disabilities have other space needs and are more specific.. Space experience, using the principle of Deaf Space design, namely 1) space and proximity, 2)  sensory reach, 3) mobility and proximity, 4)  light and color, dan 5) acoustic as a concept of implementation, is one way to create a particular space experience. As a conception of application, is one way to create a particular space experience. Deaf space design guidelines are considered an important aspect in determining design concepts and are influenced by hearing disabilities' behavioral characteristics of interiority (relations between space and humans). Context of hearing disability behavior which includes a series of stages of exploration process and interpretation by subject in it gives birth to an interiority. Interiority is the presence of oneself being able to comfort in this space. Interiority isnot merely a spatial concept, but concept in which disunited spaces can be one uniting body, mind, and space. The interiority in exhibition space toward hearing disability behavior can be implemented in design concept for hearing disability, so hearing disability users or visitors can engage in community interaction conversations and need space called "deaf space". The results of this study contribute to application of the Deaf Space design concept in DEC building toward behavior of hearing disability user, so that they can activity independently and productively.